Interdisciplinary Surgical Approaches in Vaginal and Perineal Reconstruction of Advanced Rectal and Anal Female Cancer Patients - Horch, Raymund E.; Ludolph, Ingo; Cai, Aijia; Weber, Klaus; Grützmann, Robert; Arkudas, Andreas (Frontiers in Oncology, 2020)
Relapsing or far advanced rectal and anal cancers remain difficult to treat and require interdisciplinary approaches. Due to modern standard protocols all patients receive irradiation and neoadjuvant chemotherapy – and in case of a relapse a second irradiation - rendering the surgical site prone to surgical site infections and oftentimes long lasting sinus and septic complications after exenteration in the pelvis. Despite an improved overall survival rate in these patients the downside of radical tumor surgery in the pelvis is a major loss of quality of life, especially in women when parts of the vagina need to be resected. Derived from our experince with over 300 patients receiving pelvic and perineal reconstruciton with a transpelvic vertical rectus abdominis myocutaneous (VRAM) flap we studied the impact of this surgical technique on the outcomes of female patients with or without vaginal reconstruction following pelvic exenteration. We found out that the tpVRAM flap is reliably perfused and helps to reduce long term wound healing desasters in the irradiated perineal/vaginal/gluteal region.